Systemic leadership in sustainable collaborative governance: A case study of urban green space management in Surabaya - Haryono, Nanang; Rahayu, Amy Yayuk Sri; Soeling, Pantius Drahen (Faculty of Social and Political Science, Universitas Airlangga, 2024)
Collaborative governance has been widely recognized as an effective strategy to address complex public challenges, particularly in managing urban green spaces. This research examines systemic leadership in promoting cross sectoral collaboration for sustainable urban green space management. Specifically, it explores the role of systemic leadership in fostering cross-sectoral collaboration for sustainable urban green space management in Surabaya during Mayor Tri Rismaharini’s administration (2010-2020). A qualitative case study approach was employed, involving in-depth interviews with 15 informants from various sectors, document analysis, and observations. The findings reveal that systemic leadership ensures alignment between private sector contributions and public goals. Additionally, the integration of multifunctional green infrastructure, such as pedestrian pathways and stormwater management systems, contributes to environmental sustainability and urban resilience. This study reinforces existing collaborative governance theory and highlights the importance of long-term leadership in nurturing sustainable urban green space partnerships. It concludes that systemic leadership acts as a balancing force among stakeholder interests, facilitating compromise and institutional interactions crucial to achieving collaborative goals. This research contributes to the literature by emphasizing the significance of systemic leadership in promoting sustainable urban governance and offers practical insights for policymakers and urban planners to enhance collaborative processes in similar contexts.